O silenciamento indígena na narrativa nacional conservadora de Lucas Alamán, México 1844-1849 - Barros, Gabriel Simão (2021)
The present study aims to analyze the work, “Dissertations on the history of the Mexican Republic from the time of the conquest that the Spanish people put an end to the 15th century and the early 16th century of the Islands and the American continent until independence (1844 -1849) ". VOLUME 1. From the conservative historian and politician Lucas Alamán (1792-1853), this source is understood as a response to the crisis with the present experienced by the author and by Mexico in the first half of the 19th century, marked by independence and the war against the USA. To understand the work in this way, the analysis of this source consists of the construction of the idea of European superiority in the American indigenous societies. Having the character of Hernan Cortés as its protagonist representing this superiority and Montezuma representing the inferiority